Transcriptome profiling reveals the mechanism of fruit navel development in melon (Cucumis melo L.) - Tiantian Ren; Xuqian Shi; Shuxin Zhou; Kanghui Fan; Rui Zhang; Lanchun Nie; Wensheng Zhao (BMC Plant Biology)
Abstract Background Melon is an important horticultural crop cultivated extensively worldwide. The size of the fruit navel, the terminal region of melon fruits, significantly influences the appearance quality of the fruit. However, the regulatory factors and molecular mechanisms governing the fruit navel development remain poorly understood in melon. Results In this study, the regulators and mechanisms underlying fruit navel development were investigated through phenotypic analysis, RNA sequencing (RNA-seq) and RT-qPCR methods. The inbred line ‘T03’ and a big fruit navel mutant ‘BFN’ of melon were used as experimental materials. RNA-seq analysis identified 116 differentially expressed genes (DEGs), including 54 up-regulated and 62 down-regulated genes, in both the green bud (GB) and ovary at anthesis (OA) stages of the ‘BFN’ melon compared to the ‘T03’ melon. Functional enrichment analysis revealed that these 116 DEGs were significantly associated with “Sesquiterpenoid and triterpenoid biosynthesis”, “Circadian rhythm—plant”, “Galactose metabolism” and “Biosynthesis of various alkaloids” pathways. There were three (AP2/ERF, MYB and C2H2 types) and eight (AP2/ERF, MADS-box, homeobox domain and bZIP types) transcription factors presented in up-regulated and down-regulated DEGs, and their putative target genes were predicted. Based on KEGG and expression analyses, two terpene cyclase/mutase genes (MELO3 C001812 and MELO3 C004329) were identified as being involved in the “Sesquiterpenoid and triterpenoid biosynthesis” pathway, and their transcripts were significantly downregulated in all detected development stages (EGB, GB, GYB, YB and OA) of ‘BFN’ fruits compared with ‘T03’ fruits. Conclusions The findings of this study elucidate a fundamental regulatory mechanism underlying fruit navel formation, and identify two key negative regulators, MELO3C001812 and MELO3C004329, involved in the development of the fruit navel in melon.